2017
DOI: 10.3389/fnagi.2017.00135
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Two BDNF Polymorphisms G196A/C270T in Chinese Sporadic Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is an ethnically heterogeneous motor neuron disease that results from the selective death of motor neurons in the brain and spinal cord. Brain-derived neurotrophic factor (BDNF) is widely distributed across the central and peripheral nervous systems and plays neurotrophic and other physiological roles in various brain regions. Alterations of neurotrophin availability have been proposed as a pathogenic mechanism underlying ALS neurodegeneration. Several genetic studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 60 publications
0
15
1
Order By: Relevance
“…Unlike BDNF Val66Met, the BDNF C270T polymorphism has only recently gained attention in studies of neuropsychiatric disorders ( 101 ). The T allele of the BDNF C270T polymorphism was reported to be a risk factor for PTSD ( 46 ), schizophrenia ( 29 ), bulimia nervosa ( 102 ), and amyotrophic lateral sclerosis ( 24 ), but not for Alzheimer's disease ( 78 ). The T allele prevalence in our study was 17% and it was the same as the T allele frequency in a Chinese sample with PTSD ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike BDNF Val66Met, the BDNF C270T polymorphism has only recently gained attention in studies of neuropsychiatric disorders ( 101 ). The T allele of the BDNF C270T polymorphism was reported to be a risk factor for PTSD ( 46 ), schizophrenia ( 29 ), bulimia nervosa ( 102 ), and amyotrophic lateral sclerosis ( 24 ), but not for Alzheimer's disease ( 78 ). The T allele prevalence in our study was 17% and it was the same as the T allele frequency in a Chinese sample with PTSD ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, BDNF is encoded by the BDNF gene which extends over 70 kb, located on chromosome 11, region p13–14 ( 22 ). There are hundreds of polymorphisms in the BDNF gene, however, the most frequently studied functional polymorphisms include the Val66Met single-nucleotide polymorphism (rs6265) in the coding exon ( 23 ), and the C270T single-nucleotide polymorphism (rs56164415), in the 5′-untranslated region (UTR) of the BDNF gene ( 24 ). The A (Met) allele, compared to the G (Val) allele, of the BDNF Val66Met is associated with disrupted cellular processing, trafficking and intracellular packaging of the pro-BDNF and reduced activity-dependent secretion of the mature BDNF ( 23 , 25 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SALS may result from the interaction between susceptible genes and the environment; therefore, identifying SALS susceptibility genes is as important as identifying pathogenic genes. Several previous studies have identified different susceptibility genes in various ethnic cohorts, including DPP6 , ITPR2 , UNC13A , FGGY , ELP3 , KIFAP3 , 9p21.2 , ZNF512B , TIMA1 , SCNN1A , BDNF , C21orf2 , MOBP , SCFD1 and GPX3-TNIP1 (van Es et al, 2007 , 2008 , 2009a , b ; Cronin et al, 2008 ; Landers et al, 2009 ; Simpson et al, 2009 ; Iida et al, 2011 ; Cai et al, 2014 ; Chen et al, 2014 ; van Rheenen et al, 2016 ; Xu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%